Two new species of Choroterpes Eaton (Ephemeroptera: Leptophlebiidae) from Costa Rica - A., Socorro Ávila; Flowers, R. Wills (Zootaxa, 2006)
Choroterpes gregoryi new species (type locality: Maquenco, Costa Rica) and Choroterpes mairena new species (type locality: Cuajiniquil, Costa Rica) (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) are described from imagos and nymphs. Both species occur along the west coast of Costa Rica in streams on or near the Nicoya Complex. Choroterpes mairena is adapted to living in temporary streams with long dry seasons, while Choroterpes gregoryi is found in permanent streams. Both species occur in pools with extensive leaf packs.